Determinants of the sustainability of family businesses in Benin - (:unkn) unknown (My University, 2025)
Family businesses face challenges related to succession during their expansion. Indeed, many family businesses struggle to establish mechanisms to ensure the sustainability of their organizations. These shortcomings can lead to conflicts between various stakeholders, sometimes jeopardizing the financial stability of the family business. Thus, managers must anticipate family disagreements, seeking to satisfy various stakeholders to ensure the organization's sustainability. The objective arising from this issue is to identify the determinants that contribute to the sustainability of family businesses in the Beninese context. To address this issue, we adopted the grounded theory methodology as a research strategy to develop a new theory relating to sustainability in the African context. The results indicate that managers must identify key factors that involve all stakeholders in the management of family businesses.
Keywords: African Research